33 A UNIQUE CASE OF ESOPHAGEAL PHARMACOBEZOAR IN A HUMAN IMMUNODEFICIENCY VIRUS PATIENT ON HIGHLY ACTIVE ANTIRETROVIRAL THERAPY. Issue 1 (1st January 2007) - Atwal, P.; Rehman, M.; Atwal, C.; Taj, M.; Go, E.
Abstract : Background: Bezoars result from the accumulation of ingested foreign material in the form of masses or concretions and consist of three major types depending on their composition: (1) phytobezoars (compressed vegetable matter), (2) trichobezoars (hair), (3) pharmacobezoars (compacted amounts of undigested medication). Symptoms may vary depending on the location of the bezoar. Gastric bezoars may present with abdominal pain, nausea, vomiting, early satiety, anorexia, and gastric outlet obstruction, whereas esophageal bezoars present with dysphagia, odynophagia, and regurgitation of food. Therapy for bezoars should be tailored to the composition of the concretion and to the underlying pathophysiologic process. Available treatment methods include chemical dissolution, endoscopy, or surgery. Case Report: A 56-year-old African American, female, active smoker with a history of CNS toxoplasmosis, HIV on highly active antiretroviral therapy (HAART) treatment, and bronchial asthma presented with dysphagia, odynophagia, and regurgitation of solid food. Physical examination and laboratory analysis did not reveal any significant abnormalities. The patient underwent upper GI endoscopy and was found to have a large pill bezoar (2-3 cm) occluding the lumen above a Schatzki ring. The pills were broken using a polypectomy snare and flushed into the stomach and the Schatzki ring was dilated. The patient improved symptomatically and was advised to take crushed pills/liquid medication where possible with a semisolid diet. Teaching Point: Pharmacobezoars (most commonly associated with nifedipine, ASA, sucralfate, etc) have become increasingly recognized and are typically found in the lower GI tract. Esophageal bezoars are very rare, and pharmacobezoars as a result of HAART are rarer. The potential for complications in untreated patients emphasizes the importance of early diagnosis and treatment along with prevention of recurrence.